About monotonic and oscillatory solutions of scalar linear differential equations with measures as coefficients - Wyderka, Zdzisław (Annales Mathematicae Silesianae, 1991)
The monotonic and oscillatory solutions of the first order scalar ordinary differential equations are studied. Some essential differences between the classical, Carathéodory and measures-coefficients cases are presented. Next some sufficient conditions for monotonicity or oscillations of all solutions of the equation under consideration are presented. One theorem about differential inequalities is also proved.